2014
DOI: 10.1002/lsm.22214
|View full text |Cite
|
Sign up to set email alerts
|

Miniature forward‐imaging B‐scan optical coherence tomography probe to guide real‐time laser ablation

Abstract: Background and Objective Investigations have shown that pulsed lasers tuned to 6.1 μm in wavelength are capable of ablating ocular and neural tissue with minimal collateral damage. This study investigated whether a miniature B-scan forward-imaging optical coherence tomography (OCT) probe can be combined with the laser to provide real-time visual feedback during laser incisions. Study Design/Methods and Materials A miniature 25-gauge B-scan forward-imaging OCT probe was developed and combined with a 250 μm ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Such interactive techniques are feasible, and prototypes have been demonstrated. 28,29 Coupling these techniques to a light source similar to the prototype RSA laser tested here could provide an extremely useful surgical tool.…”
Section: Discussionmentioning
confidence: 99%
“…Such interactive techniques are feasible, and prototypes have been demonstrated. 28,29 Coupling these techniques to a light source similar to the prototype RSA laser tested here could provide an extremely useful surgical tool.…”
Section: Discussionmentioning
confidence: 99%
“…OCT angiography (OCTA) images were also acquired immediately before and after ablation to monitor the laser-induced blood coagulation. Moreover, Li et al recently reported on the integration of OCT into a handheld laser ablation probe to monitor the laser incision depth [153]. Fig.…”
Section: Oct-guided Laser Surgerymentioning
confidence: 99%
“…Integration of diagnostics and therapeutics has been used in the treatment of tumorous tissue, such as the integration of ultrasound and robotic technology (27)(28)(29). OCT has been widely used in imaging to improve diagnostic accuracy and precision, and it can guide therapies via providing intraoperative in situ abundant information of tumorous tissue (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%